Fifty years after Hiroshima (2009)
Translation by Jorge Giraldo Ramírez published for the first time in Spanish with the proper authorization of the editors of John Rawls: Collected Papers, Cambridge, Mass .: Harvard University Press, 1999, pp. 565-572, edited by Samuel Freeman. Copyright